Clinical outcomes in newborns of pregnant women with COVID-19: integrative review - Iara Bezerra da Silva Ximenes; Cassiano Richel Ferreira Leal; Odinéia Maria Amorim Batista; Maria Eliete Batista Moura; Maria Zélia de Araújo Madeira; Andreia Rodrigues Moura da Costa Valle; Pedro Emílio Gomes Prates; Álvaro Francisco Lopes de Sousa; Denise de Andrade (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objectives: to analyze clinical outcomes in newborns of pregnant women with COVID-19. Methods: integrative review conducted in PubMed, Web of Knowledge, SCOPUS, CINHAL; 2,111 studies were obtained, and 8 articles comprised the final sample. Results: clinical outcomes in neonates of pregnant women positive for COVID-19 were classified according to the following categories: a) contamination by COVID-19, reported in 62.5% of the studies; b) hospital discharge due to improvement, mentioned in 37.5% of the articles; c) death, representing rare cases in 25% of the sample. The most prevalent gestational complication was prematurity, mentioned in 75% of the studies. This complication has been observed due to cases of premature rupture of membranes and placental abruption. Conclusions: despite the knowledge of asymptomatic and mildly symptomatic behavior in neonates, it is important to continue the search for new clinical data, as this public has uncertain reactions to SARS-CoV-2 infection.